2021
DOI: 10.3390/ijerph18041919
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial K-Means Clustering as a Machine Learning Tool Applied to Diabetes Mellitus Type 2

Abstract: A new original procedure based on k-means clustering is designed to find the most appropriate clinical variables able to efficiently separate into groups similar patients diagnosed with diabetes mellitus type 2 (DMT2) and underlying diseases (arterial hypertonia (AH), ischemic heart disease (CHD), diabetic polyneuropathy (DPNP), and diabetic microangiopathy (DMA)). Clustering is a machine learning tool for discovering structures in datasets. Clustering has been proven to be efficient for pattern recognition ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The importance of cluster analyses has also been highlighted by a study of Ryu et al, who developed a screening model including gender-specific characteristics for the estimation of an undiagnosed diabetes mellitus in high-risk patients for development of diabetes mellitus, namely patients with a positive family history of diabetes [ 16 ]. Additionally, more recently, Nedyalkova et al showed that k -means clustering to detect clinical variables might be useful to stratify type 2 diabetics into distinct subgroups of risk factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of cluster analyses has also been highlighted by a study of Ryu et al, who developed a screening model including gender-specific characteristics for the estimation of an undiagnosed diabetes mellitus in high-risk patients for development of diabetes mellitus, namely patients with a positive family history of diabetes [ 16 ]. Additionally, more recently, Nedyalkova et al showed that k -means clustering to detect clinical variables might be useful to stratify type 2 diabetics into distinct subgroups of risk factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nedyalkova et al (2021) applied the combinatorial k‐means algorithm for prediction the diabetes mellitus type 2. In this work, authors explore all possible aspects of k‐means algorithm with predetermined descriptor and groups.…”
Section: Related Workmentioning
confidence: 99%
“…With the advancement of electronic medical record (EMR) and artificial intelligence, machine learning (ML) approaches have been developed as part of precision medicine to assist in clinical decision-making, including disease detection, medical imaging, and explainable risk prediction [21][22][23][24][25][26][27][28][29]. In recent years, unsupervised ML algorithms have been utilized to reveal the patterns of diseases such as diabetes and cardiovascular diseases [30][31][32][33]. Consensus clustering is an unsupervised ML technique used to identify patterns of data, and provides a visualization tool to inspect cluster numbers, membership, and boundaries [34].…”
Section: Introductionmentioning
confidence: 99%